Changes in site‐scale temperature extremes over China during 2071–2100 in CMIP5 simulations. Issue 6 (25th March 2016) - Chen, Yongqin David; Li, Jianfeng; Zhang, Qiang
Abstract: Site‐scale changes in probability behaviors of temperature extremes across China during 2071–2100 are studied with general circulation models (GCMs) provided by the Coupled Model Intercomparison Project Phase 5 (CMIP5). Future temperature extremes are compared to those of 1961–2005 estimated from observed daily temperatures at 498 stations. Temperature extremes are described by 15 indices recommended by the Expert Team on Climate Change Detection and Indices; quantile mapping (QM) is used to downscale the gridded GCMs outputs to site scale. The site‐scale and grid‐scale changes of temperature extremes are compared. Results indicate that during 2071–2100, increases of daily maximum and minimum temperatures are more pronounced in the Songhua River Basin, the Liao River Basin, the Hai River Basin, the north part of the Yellow River Basin, and the Northwest Rivers. The numbers of warm days are 3 times of observations, and the warm spell durations become longer. Summer days and tropical nights, which have never been observed in the Tibetan Plateau, may occur in the future. Cold spell may disappear in the Songhua River Basin and the Liao River Basin. Compared to the grid‐scale changes, appearance or disappearance of extremes at the site scale is more obvious with higher confidence. The spatial patterns of the site‐scale and grid‐scale changes are similar, but the change rates are different to a certain extent. For extremes that are more spatially homogenous, the site‐scale and grid‐scale change rates are close. But for extremes that are more spatially heterogeneous, the site‐scale changes are more remarkable. Key Points: Site‐scale projection in temperature extremes across China Comparison of changes in temperature extremes at the site scale and the grid scale Analysis of variations in return periods in temperature extremes